1961
DOI: 10.1111/j.2042-7158.1961.tb11885.x
|View full text |Cite
|
Sign up to set email alerts
|

New Glycosides from Senna

Abstract: Sm,-The letter by Vickers in the August issue of this Journal (1961) has stimulated us to report the isolation of five anthracene glycosides from senna since our report of the separation of an active primary glycoside (Fairbairn, Friedmann and Ryan, 1958).This has been isolated from Alexandrian senna pod and appears to be similar to that reported by Vickers. We have shown it to be a rhein-monoglucoside by chemical analysis. Ultra-violet absorption measurements indicate that the compound is identical with synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Zwaving (27) found only dianthrone glyco sides, accompanied by small quantities of the related anthraquinone glucosides, but no mono-anthrone glycosides in the dried leaves. Other authors (10,26) found comparatively small quantities of anthrone glucosides or aglycones in the leaves; only one of them found a mono-anthrone glucoside also in the pods (3).…”
Section: Anthraquinone Drugs and Their Componentsmentioning
confidence: 99%
“…Zwaving (27) found only dianthrone glyco sides, accompanied by small quantities of the related anthraquinone glucosides, but no mono-anthrone glycosides in the dried leaves. Other authors (10,26) found comparatively small quantities of anthrone glucosides or aglycones in the leaves; only one of them found a mono-anthrone glucoside also in the pods (3).…”
Section: Anthraquinone Drugs and Their Componentsmentioning
confidence: 99%
“…Equivalent weight determination indi cated that it was an even larger molecule than that described above; the compound was deacetylated, but not further purified, and its biological activity shown to be about twice that of sennosides on a molar basis. Later, Crellin et al (1961) reported briefly on a further primary glycoside with a molecular weight of about 2,000. Schmid and Angliker (1965) criticised this work and claimed that these primary glyco sides were mixtures of normal senna glycosides: the fact that they were mixtures imparted extra water solubility and enhanced biological activ ity.…”
Section: Sulphated Glycosidesmentioning
confidence: 99%
“…Unspecified aloe-emodin glycosides have been reported from Cassia senna L. (Rai et al, 1974), Cassia angustzfolia Vahl. (Crellin, Fairbairn, Friedmann & Ryan, 1961;Zwaving, 1965Zwaving, , 1974 and Rheum palmatum (Horhammer, Wagner & Leue, 1959;Zwaving, 1965Zwaving, , 1974. Chrysophanol-8-P-D-glucoside has been detected in Asphodelus microcarpus Salzm.…”
mentioning
confidence: 99%
“…Uncharacterized dianthrone glycosides have been found in Rhamnuspurshiana bark (Kinget, 1968). More complex compounds containing the sennoside molecule with additional sugar units have been described from senna (Crellin et al, 1961;Fairbairn, 1964;Fairbairn, Friedmann & Ryan, 1958).…”
mentioning
confidence: 99%